(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The scientific work has analyzed literary and Internet sources on the selected research topics, which allowed us to identify certain shortcomings in domestic information and literary sources regarding modern and innovative means of registering technical and tactical actions of football players of different ages. As part of the experiment, a pedagogical experiment was conducted using statistical systems and programs Wyscout, Polar, Catapult and involving professional football players. The experimental study consisted of conducting a detailed analysis of various statistical data of football players during competitive activities. A comparative analysis of three matches of the Second League of the Ukrainian Football Championship in which the team of the Nyva Ternopil Football Club participated was conducted. In our work, we managed to analyze modern technologies for using programs, namely InStat, Polar, Catapult, Microgate, Wyscout, Micoach and others. The work thoroughly and in detail studied and analyzed the results of the most informative and popular data on technical and tactical actions of football players using the Wyscout, Polar, Catapult programs. The obtained data are an important tool for the future effective activity of coaches and analysts of teams of different ranks. The feasibility of regular and systematic use of the Wyscout, Polar, Catapult programs for analyzing technical and tactical actions of football players of different ages has been confirmed and substantiated. Electronic registers of the Wyscout, Polar, Catapult programs allow determining key game indicators and their dynamics during the game, which can be obtained after individual games or each game, about future opponents, and comparing data from different matches.